2013
DOI: 10.1007/s11033-012-2396-z
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the association of glutathione S-transferase P1 gene polymorphism with the susceptibility of breast cancer

Abstract: Glutathione S-transferase P1 (GSTP1) is one of the important mutant sites for the cancer risk at present. The conclusions of the published reports on the relationship between GSTP1 A/G gene polymorphism and the risk of breast cancer are still debated. This meta-analysis was performed to evaluate the association between GSTP1 and the risk of breast cancer. The association reports were identified from PubMed and Cochrane Library, and eligible studies were included and synthesized using meta-analysis method. 35 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…Zhang et al (2011) reported that the minor allele homozygotes of rs1695 (GG) were associated with an increased risk of developing BC, which is consistent with three other studies in Chinese women (Chang et al, 2006;Lee et al, 2008;Sakoda et al, 2008). Liu et al (2013) found that GSTP1 rs1695 was associated with BC risk in an Asian population, but not in Caucasians or Africans. In our data, the SNP in rs1695 was found to be associated with an increased BC risk among heterozygote carriers, which is similar to the results of Zhang et al (2011).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Zhang et al (2011) reported that the minor allele homozygotes of rs1695 (GG) were associated with an increased risk of developing BC, which is consistent with three other studies in Chinese women (Chang et al, 2006;Lee et al, 2008;Sakoda et al, 2008). Liu et al (2013) found that GSTP1 rs1695 was associated with BC risk in an Asian population, but not in Caucasians or Africans. In our data, the SNP in rs1695 was found to be associated with an increased BC risk among heterozygote carriers, which is similar to the results of Zhang et al (2011).…”
Section: Discussionsupporting
confidence: 83%
“…Reding et al (2009) showed that the GSTP1 rs1695 A allele was a protective factor for BC compared with the G allele, but several other studies found no association between rs1695 and BC risk (Ramalhinho et al, 2011;Liu et al, 2013). Zhang et al (2011) reported that the minor allele homozygotes of rs1695 (GG) were associated with an increased risk of developing BC, which is consistent with three other studies in Chinese women (Chang et al, 2006;Lee et al, 2008;Sakoda et al, 2008).…”
Section: Discussionsupporting
confidence: 72%
“…Our results provide greater confidence because of the larger number of studies included than that in previous relative meta-analyses (Liu et al, 2013). However, some limitations must be taken into consideration.…”
Section: Discussionmentioning
confidence: 54%
“…Hereditary factors including high-and moderate-penetrance genes have been identified in only about 20% of the total cases of BC (Stratton and Rahman, 2008); that is, most cases of BC are closely bound with common mutations in low penetrance genes. Also, interactions between carcinogenic agents such as estrogen are related to BC (Lynch et al, 2008;Palacios et al, 2008;Hemel and Domchek, 2010). CEMP plays an important role in the estrogen metabolism process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation